Etiology and clinical characteristics of influenza-like illness in healthy adults by hospitalization status. (4th October 2017) - Maves, Ryan; Chen, Wei-Ju; Fairchok, Mary; Schofield, Christina; Arnold, John; Danaher, Patrick; Deiss, Robert; Lalani, Tahaniyat; Rajnik, Michael; Malone, Leslie; Grigorenko, Elena; Stalons, Donald; et al.
Abstract: Background: Viral respiratory infections are a common cause of hospitalization for younger, otherwise-healthy populations. In this study, we describe the epidemiology of influenza-like illness in non-elderly adults within the U.S. Military Health System (MHS) by pathogen and hospitalization status. Methods: The Acute Respiratory Infection Consortium (ARIC) is a prospective cohort of patients with influenza-like illness within the MHS. Participants between 18 and 65 years of age were identified in outpatient settings between 2012 and 2017, and were excluded if pregnant, if reporting chronic cardiac, respiratory, renal, or neurologic disease, or if on long-term aspirin therapy. Demographics, nasopharyngeal swabs and symptom data were collected; swabs were tested for viral pathogens using a target-enriched multiplex PCR panel (TEM-PCR TM, Diatherix LLC). Data were analyzed to compare clinical features and risks for hospitalization. Results: 397 participants met inclusion criteria. 34 participants required hospitalization; 363 were outpatients. Median length of hospitalization was 2 days. A virus was identified in 58.4% of outpatients (OP) and 55.9% of inpatients (IP); coronaviruses (63/363), enteroviruses (50/363), and influenza A (73/363) predominated in OP, whereas influenza A predominated among IP (35.3%, 12/34). There were no significant differences between OP and IP in terms of age, gender, ethnicity, or tobacco use. IP were more likely to be obese (BMI ≥30, 43.3% vs. 20.5%, P = 0.004) and less likely to have received influenza vaccination (45.5% vs. 16.9%, P > 0.001). IP with influenza did not report more severe symptoms (chills, cough, sore throat, diarrhea, myalgia, or headache) on enrollment but were more likely to have fever (temperature ≥38.0⁰ C) than OP (92.9 vs. 57.1%, P = 0.014). Conclusion: Influenza A is the most frequently identified cause of hospitalization among healthy, non-elderly adults with viral respiratory infection. Although age and tobacco use may be risks for viral acquisition, they do not appear to increase the risk of hospitalization in infected patients. Non-obese BMI and influenza vaccination appear protective against hospitalization, even in a relatively healthy cohort. Disclosures: L. Malone, Diatherix Laboratories: Employee,  Salary; E. Grigorenko, Diatherix Laboratories: Employee,  Salary; D. Stalons, Diatherix Laboratories: Employee, Salary